What Phonological Facilitation Tells about Semantic Interference: A Dual-Task Study - Ayora, Pauline; Peressotti, Francesca; Alario, F.-Xavier; Mulatti, Claudio; Pluchino, Patrick; Job, Remo; Dell'Acqua, Roberto (Frontiers in Psychology, 2011)
Despite increasing interest on the topic, the extent to which linguistic processing demands attentional resources remains poorly understood. We report an empirical re-examination of claims about lexical processing made on the basis of the picture-word interference task (PWI) when merged in a dual-task psychological refractory period (PRP) paradigm. Two experiments were conducted in which participants were presented with a tone followed shortly after (at varying stimulus onset asynchronies or SOA) by a picture-word stimulus. In Experiment 1, the phonological relatedness between pictures and distractors was manipulated. Begin- and end-related distractors decreased picture naming latencies relative to unrelated distractors, constantly across SOAs. This additive pattern indicates that distractor words are processed in this PRP paradigm, irrespective of SOA. In Experiment 2, both the semantic and the phonological relatedness between pictures and distractor were manipulated. Replicating Experiment 1, the phonological manipulation yielded an additive pattern which contrasted with the under-additive pattern observed for the semantic interference effect. This contrastive pattern unambiguously indicates that the phonological and semantic interplay between pictures and words takes place at different processing stages, the later being associated to an early, pre-central stage of processing. Given the relevance of the picture-word interference task for current research in the field, these findings impose a significant constraint for language production models.